HOUSEHOLDS’ ADAPTATION TO INFRASTRUCTURE DEFICIT IN ILE-IFE, NIGERIA - David Oluwasegun Mobolaji; Oluwole Daramola; Seun Popoola; Oluwatobi Tajudeen (Department of Urban and Regional Planning, Faculty of Engineering, Diponegoro University, 2025)
In Nigeria, low quality of life is an indication of failure in infrastructure provision by government. Households therefore adapt as a coping strategy to infrastructure deficit in Ile-Ife, one of the traditional cities in Nigeria. Using multistage sampling procedures, residential areas in Ile-Ife were stratified into developmental zones comprising the core, transition and suburban. Due to homogeneity in each zone, one residential area was randomly selected in each of the three zones from which 117 residential buildings were systematically selected. Target respondent for questionnaire administration was any household member above 18 years of age from each selected building. Findings from the study revealed that similarity exists in the level of household’s infrastructure deficit across the developmental zones. However, households’ adaptation to infrastructure deficit varied across the developmental zones as determined by socioeconomic characteristics such as income, although respondents in the suburban zone adapted more to infrastructure deficit than those in the core and transition zones. The study recommended that community-based organizations, philanthropists and international organisations should complement the effort of government in the provision of infrastructure across the three developmental zones.